Pengaruh Media Pembelajaran Flashcard Terhadap Hasil Belajar Kognitif Siswa Pada Materi Hidrosfer Di Kelas X Sman 54 Jakarta - Azzahra, Anisa; Lestariningsih, Dwi Sukanti; Sucahyanto, Sucahyanto (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to determine the effect of Flashcard learning media on the learning outcomes of class X students on the hydrosphere material in Geography subject at SMAN 54 Jakarta. This study used an experimental research method with a quasi-experimental design. The population in this study were students of class X SMAN 54 Jakarta with research samples taken through purposive sampling, namely class X-C as an experimental class that carried out the learning process using Flashcard media and class X-D as a control class that used Powerpoint media accompanied by pictures. The results showed that there was an effect of Flashcard learning media on the learning outcomes of class X students. This was evidenced by the average Post-Test score of the experimental class which was higher than the average Post-Test score of the control class. The Post-Test values of both classes were then tested through the Independent Sample T-Test with a significance level value (Sig.) of 0.01 < 0.05 which stated that H0 was rejected and Ha was accepted. This means that there is a significant difference between the post-test results of the control class and the post-test results of the experimental class.